Assessing the Demand for Food in Europe by the Year 2010 - Leon Podkaminer (The Vienna Institute for International Economic Studies (wiiw), 2004)
Data on household consumption provided by the European Comparison Project for 1999 are used to estimate the parameters of the cross-country Almost Ideal Demand System (AIDS) for two aggregates food and non-food. The estimates are highly significant. AIDS specified with parameter estimates is used for assessing food demand in 2010. Four alternative price trends are considered, each assuming 2% real per capita income growth p.a. in Western Europe and 4% in 12 EU accession countries (ACs). Food consumption will be rising 2.6% p.a. in ACs, and the ACs' share in all-Europe food consumption will increase from 13.6% (1999) to 16-17% (2010).
Keywords: R22; C53; D12; Q11; 330; cross-country demand functions; Almost Ideal Demand System; food consumption; European Comparison Project